2014
DOI: 10.1007/s00059-014-4155-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of fQRS in coronary artery disease

Abstract: Based on current evidence, fQRS was associated with increased MACE, mortality, Q waves, anterior-wall MI, and decreased LVEF in CAD. These findings show that fQRS is a reliable marker in CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…Recently, fQRS has been reported more in its prognostic effects of poor clinical outcomes in several cardiac conditions (Bonakdar et al, 2016;Das et al, 2010;Rattanawong et al, 2017;Xu et al, 2015). Suggested mechanism of fQRS is explained by electrical dyssynchrony of interventricular conduction (Sinha et al, 2016), which could result from a myocardial scar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, fQRS has been reported more in its prognostic effects of poor clinical outcomes in several cardiac conditions (Bonakdar et al, 2016;Das et al, 2010;Rattanawong et al, 2017;Xu et al, 2015). Suggested mechanism of fQRS is explained by electrical dyssynchrony of interventricular conduction (Sinha et al, 2016), which could result from a myocardial scar.…”
Section: Discussionmentioning
confidence: 99%
“…Fragmented QRS (fQRS), which reflects myocardial scarring, has been found to be associated with poor prognostic outcome in several cardiac conditions, including coronary artery disease (Xu et al, 2015), non-ischemic cardiomyopathy (Das et al, 2010), Brugada syndrome (Rattanawong et al, 2017), chronic total occlusion (Bonakdar et al, 2016), and hypertrophic cardiomyopathy (Rattanawong et al, 2018). Recent studies have demonstrated poor prognostic outcome in HFrEF patients whose baseline ECG was positive for fQRS.…”
Section: Introductionmentioning
confidence: 99%
“…This prevalence is considerably higher than in the general population-where it is just over 5%. 12,27,28 The presence of QRS fragmentation was associated with larger MIs as measured by total serum creatine kinase levels (1438.0 vs. 1160.0 U/L, p = .039) and with slightly lower left ventricular ejection fraction (52% vs. 54%, p = .011). In addition, the QRS complexes of patients with fragmentation were significantly wider than those of patients without QRS fragmentation (90 vs. 85 ms, p < .001).…”
Section: Discussionmentioning
confidence: 96%
“…Recently, fragmentations of the QRS complex (fQRS) in resting 12-lead electrocardiograms (ECG) have been discussed as a potential simple risk predictor in cardiac patients. [12][13][14][15][16][17][18] Narrow QRS complexes with an unremarkable morphology are found in patients with a normal electrical excitation propagation in the ventricles. If the electrical excitation propagation is impaired, for example, due to areas of myocardial fibrosis or scar, 13,19 cardiomyopathies, 20 channelopathies, 21,22 or systemic diseases with cardiac involvement such as sarcoidosis, 23 QRS morphology can be altered or fragmented.…”
Section: Introductionmentioning
confidence: 99%
“…По данным метаанализа, включившего 16 обсервационных исследований (3997 пациентов с ИБС), вероятность развития переднего инфаркта повышалась более чем в 2 раза при наличии fQRS (ОШ = 2,4; 95%-й ДИ: 1,1-5,5; p = 0,03). В свою очередь, частота развития крупных сердечно-сосудистых катастроф и смертность оказались значимо выше в группе с fQRS в сравнении с группой без fQRS (соответственно ОШ = 3,2; p < 0,00001 и ОШ = 2,2; p < 0,0001) [28].…”
Section: Fqrs -предиктор неблагоприятного течения ибсunclassified